Type I Tympanoplasty - Jolien Euben; Sandrine Machiels; Nicolas Mardyla (B-ENT)
When an ENT surgeon plans on starting the endoscopic technique for ear surgery, type I tympanoplasty is the first intervention to master. We wish to discuss the advantages and difficulties of the use of the endoscope, and offer a description of type I tympanoplasty as we realize it.